Early life microbiota transplantation from highly feed-efficient broiler improved weight gain by reshaping the gut microbiota in laying chicken - Elokil, Abdelmotaleb A.; Chen, Wei; Mahrose, Khalid; Elattrouny, Mahmoud M.; Abouelezz, Khaled F. M.; Ahmad, Hafiz Ishfaq; Liu, Hua-Zhen; Elolimy, Ahmed A.; Mandouh, Mahmoud I.; Abdelatty, Alzahraa M.; Li, Shijun (Frontiers in Microbiology, 2022)
Starting phase of laying chicken life is the building stone for rearing and production stages. Since, fecal microbial transplantation (FMT) regulates the gut microbial diversity and affects the productive performance of the bird. The aim of this study is to evaluate the effect of FMT from feed-efficient broiler chicken could program the diversity of gut microbiota and growth of recipient native slow growing egg-laying chicks. For this, a total of 150 (one-day-old) Jing Hong chicks were randomly assigned into two groups, each group consisted of 5 replicates (n = 15 bird/ replicate). The control group (CON) and FMT recipient birds (FMT) fed on basal diet, the FMT group received an oral daily dose of FMT prepared from Cobb-500 chickens. The FMT performed from the 1d to 28d of age, through the experimental period, feed intake and body weight were recorded weekly. At the end of a 28-day trial, carcass traits were assessed and cecal samples were collected for microbiome assessment via 16S rRNA-based metagenomic analysis to characterize the diversity and functions of microbial communities. The data were statistically analyzed using R software. Body weight and body weight gain increased, and FCR decreased (p = 0.01) in FMT group. The relative abundance of Firmicutes and the Firmicutes/Bacteroidetes (F/B) ratio were increased due to FMT administration (p = 0.01). A higher relative abundance of Lactobacillus, Lactococcus, and Bifidobacterium were presented in the FMT group. Meanwhile, Enterococcus, Helicobacter, and Bacteroides were more abundant in the CON group (p < 0.01). Kyoto encyclopedia of genes and genomes (KEGG) pathways for microbial functions regarding amino acid metabolism, secondary metabolites biosynthesis, carbohydrate metabolism, energy metabolism, and enzyme families, cofactors, and vitamins were significantly annotated in the FMT group. Overall, FMT administration from the donor of highly feed-efficient broilers improved weight gain by reshaping a distinct gut microbiome, which may be related to the metabolism and health in the recipients laying chicks, providing new insight on the application of the FMT technique for early life programming of laying chickens.